Patient with COVID – 19 infection presenting with acute 6th cranial nerve palsy: A case report (Bangladesh Critical Care Journal, 2020)
We present a case of a 55 year old lady, hypertensive and diabetic who was infected with COVID-19 presenting with acute 6th cranial nerve palsy. The patient was diagnosed with COVID-19 on Sept 01 2020. Seven days later she developed double vision and headache. At that point on complete neurological examination including examination of cranial nerves she was found to have 6th cranial nerve (Abducens) palsy with convergent squint. As the patients cranial nerves were all intact initially it is suspected that her 6th nerve palsy was related to the viral illness. She was assessed by ophthalmologist and neurologist. She underwent MRI scan of the brain to look for other causes of 6th nerve palsy and it was unremarkable. After almost one week of continued inpatient management her diplopia improved but she still complained of intermittent diplopia with convergent squint.Bangladesh Crit Care J September 2020; 8(2): 129-130